Tinjauan Sistematis Untuk Merekomendasi Prediksi Harga Emas - RIZKI KRISTIA AKMAL (Jurnal Inovasi Informatika, 2022)
Gold is one of the precious metals that can be used as investment material, because the price is always stable. So that investors try to predict the price of gold for the future. There are various methods for predicting gold prices, but not all methods can predict gold prices with accuracy. This study was written using the PRISMA method to find the right method to predict gold prices. The research shows that the Fuzzy Time Series method is a method that is often used to predict gold prices, because this method can capture patterns from previous data and then use it to predict the future by determining the length of the interval at the beginning, because the length of the interval is very influential to get accurate prediction results.